Beta human papillomavirus 8 E6 deregulates double strand break repair - Hu, Changkun (Kansas State University, 2022)
Beta human papillomaviruses are hypothesized to promote nonmelanoma skin cancer by deregulating DNA repair pathways. Most of the molecular evidence that [Beta]-HPV impairs DNA repair has been gained via characterization of the E6 protein from [Beta]-HPV 8 (8E6). By reducing p300 availability, 8E6 attenuates a major double-strand DNA break (DSB) repair pathway, homologous recombination. We show that 8E6 impairs another DSB repair pathway, non-homologous end joining (NHEJ). HR and NHEJ are not thought to occur in the same cell at the same time. HR is restricted to cells in phases of the cell cycle where homologous templates are available, while NHEJ occurs primarily during G1. We found that 8E6 causes colocalization of HR factors (RPA70 and RAD51) with an NHEJ factor (activated DNA-PKcs or pDNA-PKcs) at persistent DSBs. 8E6 also causes RAD51 foci to form during G1. Further, we used next-generation sequencing of the 200kb surrounding a CAS9-induced DSB to show that 8E6 caused a 21-fold increase in deletions. Chemical and genetic inhibition of p300 as well as an 8E6 mutant that is incapable of destabilizing p300 demonstrated that 8E6 is acting via p300 destabilization. More specific chemical inhibitors of DNA repair provided mechanistic insight by mimicking 8E6-induced dysregulation of DNA repair in a virus-free system. Specifically, inhibition of NHEJ causes RAD51 foci to form in G1 and colocalization of RAD51 with pDNA-PKcs. Finally, we show that 8E6 promotes a backup DSB repair pathway, alternative end-joining (Alt-EJ). Using CAS9 and transfection-based reporters, we found that 8E6 promotes both DNA resection-dependent and independent Alt-EJ. Together, these studies expand the knowledge that [Beta]-HPV deregulate DNA repair pathways and increases genomic instability. Moreover, we provide novel methods and tools for fundamental research in DNA repair fields.
Keywords: Beta-HPV; DNA repair; NHEJ; HR; MMEJ; P300